Golgi Apparatus: A Potential Therapeutic Target for Autophagy-Associated Neurological Diseases - Deng, Shuwen; Liu, Jia; Wu, Xiaomei; Lu, Wei (Frontiers in Cell and Developmental Biology, 2020)
Abstract Autophagy has dual effects in human diseases: appropriate autophagy may protect cells from stress, while excessive autophagy may cause cell death. Additionally, close interactions exist between autophagy and the Golgi. This review outlines recent advances regarding the role of the Golgi apparatus in autophagy. The signaling processes of autophagy are dependent on the normal function of the Golgi. Specifically, (i) autophagy-related protein 9 is mainly located in the Golgi and forms new autophagosomes in response to stressors; (ii) Golgi fragmentation is induced by Golgi-related proteins and accompanied with autophagy induction; and (iii) the endoplasmic reticulum-Golgi intermediate compartment and the reticular trans-Golgi network play essential roles in autophagosome formation to provide a template for lipidation of microtubule-associated protein 1A/1B-light chain 3 and induce further ubiquitination. Golgi-related proteins regulate formation of autophagosomes, and disrupted formation of autophagy can influence Golgi function. Notably, aberrant autophagy has been demonstrated to be implicated in neurological diseases. Thus, targeted therapies aimed at protecting the Golgi or regulating Golgi proteins might prevent or ameliorate autophagy-related neurological diseases. Further studies are needed to investigate the potential application of Golgi therapy in autophagy-based neurological diseases.